Psychological effects of circumcision as practiced in Turkey - Öztürk, Orhan M. (The Turkish Journal of Pediatrics, 1963)
In Turkey, children are circumcised without anesthesia at ages which are most critical from the psychosexual point of view. Psychoanalytical theory would lead one to deduce that Turkish children, particularly rural children, may be experiencing serious trauma right in the midst of resolving Oedipal conflicts and castration anxieties. However, it is as if the society had realized this and had therefore instituted ways and means to make this specific experience an ego-strengthening process. The child’s pain and loss are minimized by adequate preparations and counterphobic defenses and are well rewarded by ceremonies, gifts and the status gained. Two cases which illustrate the implications of poorly handled circumcision in psychopathology are presented. This is a preliminary report of a long-term research project.